Stress Management in Primary Caregivers: A Health Challenge - Aguiló, Sira; Lopez-Barbeito, Beatriz; García, Esther; Aguiló, Jordi (Transactions on Engineering and Computing Sciences, 2017)
Technology based advances in healthcare are leading to social changes that, in turn, will require innovative responses from health systems. Mainly due to these advances, life expectancy grows so, the aging of world population increases and with it the percentage of chronic patients. Because ofthese two factors: aging people and chronic patients, new needs are posed to the current health system. Together with these patients,a population of non-professional caregivers emerges playing a key role in the care process. However, the impact of the care burden on their health is usually underminedalthough an increasing number of studies report caregiver associated diseases. One of the challenges that arise from health systems: To acknowledgeand to take care this population of caregivers,to avoid the so-called burned caregiver syndrome as well as to reduce the risks of comorbidities associated with the caregiver's stress by setting up appropriate interventions. Having in mind all these considerations, from the Clinic Hospital in Barcelona we are starting to work ona biofeedback program involvingdifferent populations of caregivers: 30 caregivers of oncological patients and 30 caregivers of geriatric patients and the corresponding control group. The project that is presented in this paper is aiming to determine if these therapies can become effective interventions to reduce the stress that represents the caregiver syndrome. The follow-up of the project willfocus on the possibility to indirectly demonstrate if the decrease of stress actually results in a decrease of the derived diseases and of the total cost that it entails.